1988
DOI: 10.1007/bf02623602
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of continuous avian cell lines depleted of mitochondrial DNA

Abstract: Populations of quail and chicken cells were treated with ethidium bromide, an inhibitor of mitochondrial DNA replication. After long-term exposure to the drug, the cell populations were transferred to ethidium bromide (EtdBr)-free medium, and cloned. Clones HCF7 (quail) and DUS-3 (chicken) were propagated for more than a year, and then characterized. Analysis of total cellular DNA extracted from these cells revealed no characteristic mitochondrial DNA molecule by Southern blot hybridization of HindIII- or AvaI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…One effect of cells devoid of mtDNA is slowed proliferation (61). At the cellular level, using our inducible knockdown system, we monitored the gradual reduction of SUV3 expression (with a robust knockdown efficiency of Ͼ90%) and observed multinucleation and senescence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One effect of cells devoid of mtDNA is slowed proliferation (61). At the cellular level, using our inducible knockdown system, we monitored the gradual reduction of SUV3 expression (with a robust knockdown efficiency of Ͼ90%) and observed multinucleation and senescence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lower animals, plants and fungi can use alternative ways to reduce and oxidize CoQ, such as NADH-DH/CoQ reductase activity or CoQ oxidase activity, albeit without proton translocation (2,3). Vertebrate cells lacking a functional mtETC owing to the absence of mtDNA (°cells), can be maintained in culture if supplemented with uridine and pyruvate (4,5). NDI1 and AOX are monopeptidic enzymes with NADH DH/CoQ reductase and CoQ/O 2 oxidase activities, respectively, that do not translocate protons.…”
mentioning
confidence: 99%
“…During the 1970s and 1980s it was shown that chronic exposure to cationic DNA mutagens, such as ethidium bromide, can selectively block mtDNA replication (84,160). Selective mtDNA toxicity in this case results from the fact that cationic mutagens concentrate FIG.…”
Section: What Are Cybrids?mentioning
confidence: 99%
“…Because before its identification as mtDNA cytoplasmic DNA was referred to as q DNA (30), cell lines completely depleted of endogenous mtDNA are typically called q0 cells. First, it was shown that mtDNA-depleted cells require uridine (84). The accepted reason for this is that one step of the pyrimidine de novo pathway, the dihydorotate dehydrogenase-mediated dehydrogenation of dihydroorotate to orotate, is coupled to the reduction of ubiquinone to ubiquinol (51,84,150,163).…”
Section: Fig 2 Complex I Is Part Of the Etcmentioning
confidence: 99%
See 1 more Smart Citation